The Interaction Between Microbiota and Stem Cells on Progression of Osteoarthritis and Engineered Stem Cell for Enhancing Osteoarthritis Treatment - Wang S; Fu H; Xu Z; Huang C (International Journal of Nanomedicine)
Sidan Wang,1 Haotian Fu,1 Zheng Xu,2 Chunhong Huang3 1Queen Mary School, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China; 2Department of Rehabilitation, Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, 330000, People’s Republic of China; 3School of Basic Medical Sciences, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of ChinaCorrespondence: Chunhong Huang, School of Basic Medical Sciences, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China, Tel +86 15507587641, Email chhuang@ncu.edu.cn Sidan Wang, Queen Mary School, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China, Tel +86 13720228749, Email stacy_wang2003@sina.comAbstract: Osteoarthritis (OA) is characterized by the degeneration of articular cartilage caused by several factors of which novel most trends include microbiota. Specific microbiota and the role in the development of OA is less clear. The microbiota is presumed to influence OA occurrence and progression mainly via immune modulation. In recent years, bone marrow mesenchymal stem cells (MSCs) have shown great potential for the treatment of OA, however, the therapeutic efficiency has been seriously affected by the harsh microenvironment in the joint cavity. At present, many strategies have been used to enhance the function of MSCs, among them, engineering are a promising method. Therefore, this review mainly focuses on the latest research on how the microbiota affects the development of OA, stem cell repair, and the use of engineered MSCs in the treatment of OA. In addition, engineered MSCs can enhance the therapeutic potential of exosomes as a novel strategy for treating OA. Our review provides a comprehensive perspective on the role of microbiota in OA and the influence of MSCs therapy and engineered MSCs on the treatment of OA.Keywords: microbiota, microenvironment, engineering bone marrow mesenchymal stem cell, osteoarthritis, repair